The Irrationality of Consumers Choosing Plane Tickets : Case Study of Generation Z Representatives in the Czech Republic - Pojkarová, Kateřina; Gottwald, Dalibor (My University, 2020)
Economic models can be used to describe consumer behaviouror to predict expected behaviourof the consumers. In order for the application of the selected economic model to describe realistically the issue under study, it is necessary that the individual components of the economic model are able to reliably identify and possibly even quantify main characteristics of the studied problematique. In the last few years, one of the basic theses based on which several economic models are built upon has been "questioned" within the scientific community, namely the one that portraits human as always rationally behaving individual. The goal of this article is to verify the validity of rational choice theory, based on as sample of university students in the Czech Republic that are currently enrolled at the Faculty of Transport Engineering, University of Pardubice.To validate the theory of irrationality in the context of consumer behaviour, an experiment in the fieldof air transport will be used, monitoring consumer decision making while choosing the plane tickets.
Iracionalita cestujících v letecké dopravě při rozhodování o nákupu letenek: případová studie reprezentantů generace Z v České republice
Keywords: rational choice theory; passengers, air transport; decision making; irrational decisions; teorie racionálního volby; cestující; letecká doprava; rozhodování; iracionální rozhodnutí